Representasi Peran Ibu Ideal Dalam Islam Pada Film Ali Dan Ratu-Ratu Queens - M Yakub; Melisya Febi Damayanti; Indah Fadhilla (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2023)
Islam teaches humans to glorify a mother. In carrying out the role of a mother, women face various challenges. A mother's struggle to become an ideal mother can be seen in the scenes in the film Ali and Ratu-Ratu Queens. The representation of the mother's role is seen by using representation theory through the meaning of the scenes that highlight the character of the mother. The approach used in this research is qualitative by using Stuart Hall's representation theory in data collection techniques using observation and documentation. From the results of this study, it can be concluded that the meaning of the mother's role in the film Ali dan Ratu-Ratu Queens is as an educator, a friend, a protector, and as a role model. These roles are part of the intrapersonal communication model of a mother to her child. This research is critical because the film is one of the da'wah media. Even though this film is not a film with a religious theme, this film has a very sharp meaning in representing the communication between mother and child to portray the ideal role of mother in Islam..